Penyelesaian Hukum Terhadap Nasabah Lembaga Keuangan Bukan Bank Yang Terdampak Pandemi Covid-19 - Waremra, Merlin Clara; Berlianty, Teng; Pariela, Marselo Valentino Geovani (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Bunas Finance Indonesia (BFI) is a company that serves loans with vehicle and house certificate guarantees, therefore Bunas Finance Indonesia (BFI) provides credit to customers with a period ranging from 12 months to 48 months or depending on the loan product chosen by the customer, if the customer experiences a delay in payment, a fine of 0.5% or 0.3% per day of the loan made. However, currently the world has been hit by an Extraordinary Event in the form of the Covid-19 pandemic caused by the SARS-CoV-2 virus which infected the first individual in Wuhan and then spread to all corners of the world, including IndonesiaPurposes of the Research: This study aims to determine and explain the effect of the Covid-19 pandemic on Bunas Finance Indonesia (BFI) customers in carrying out payment obligations. To find out and explain legal settlements for customers of Bunas Finance Indonesia (BFI) as a non-bank financial institution affected by the Covid-19 pandemicMethods of the Research: This research is legal research. This research is normative legal research or library law research where it is in the form of legal theory, studied data, laws and regulations, and court decisions.Results of the Research: From the results of the research, companies that provide Bunas Finance Indonesia (BFI) can be held accountable for defaulting on customers in financial settlements so that customers can get the vehicles they own.